Protocol for in vitro selection of potatoe plants resistant to Alternaria solani Sor. culture filtrate - Novisel Veitía; Lourdes R. García; Idalmis Bermúdez-Caraballoso; Mayra Acosta-Suárez; Michel Leiva-Mora; Yelenys Alvarado-Capó; Dámaris Torres; Yenny Padrón (Biotecnología Vegetal, 2009)
The use of culture filtrate of Alternaria solani in the differentiation of susceptible and resistant potato genotypes has been described in scientific literature. However, few researches take into account the role of isolates of A. solani and other factors affecting the production of culture filtrate to use in vitro selection as a tool. This allows plant breeders to reduce the time to obtained new varieties of potato. This study aimed to establish a protocol for in vitro selection of potato plants resistant to early blight with the use of culture filtrate of Alternaria solani Sor, in support to the potato Genetic Improvement Program. The proposed protocol related aspects such as: obtaining of culture filtrate, characteristics of A. solani isolates and plant material, as well as, the descriptive scale for assessing the effect of culture filtrate on potato plants (Solanum tuberosum L.) var. Desirée. The protocol can be used as a useful tool in early stage trials to evaluate the resistance to A. solani in potato genotypes obtained by any method of genetic improvement to this disease. This contributes to increased efficiency of selection in natural conditions. The number of individuals to evaluate in field decreases. In these conditions other factors affect the differentiation of susceptible and resistant genotypes. Keywords: Desirée, breeding program, early blight